Analisis Usahatani Padi Pupuk Organik dan Pupuk Non Organik di Subak Jaka, Desa Kukuh, Kecamatan Marga, Kabupaten Tabanan (Jurnal Agribisnis dan Agrowisata, 2025)
Analysis of Organic Fertilizer Rice and Non Organic Fertilizer Rice Farming in Subak Jaka, Kukuh Village, Marga District, Tabanan Regency. Rice is a crop commodity needed by the majority of the Indonesian population as a food producer in the form of rice. Rice is a commodity that is very widely cultivated by the Indonesian population with the aim of obtaining products that can be useful for personal consumption or sold for financial gain. Rice cultivation as a source of food makes rice necessary to always be cultivated with the aim of meeting the increasing level of consumption along with the increasing population. This study aims to determine the level of production, income, BEP, and r-c ratio of farming. Data collection is done through interviews, surveys, and documentation methods. The study sample was calculated using the slovin formula. The data in this study used quantitative and qualitative data, the data was analyzed using descriptive analysis methods and feasibility analysis. The results of the analysis showed the production rate of organic fertilizer rice 6,000 kg/ha and non-organic fertilizer rice 5,994 kg/ha. Calculation of income level of organic fertilizer rice Rp20.877.165,67/ha and non-organic fertilizer rice Rp21.241.257,31/ha. The r-c ratio of organic fertilizer rice is 2.58 and non-organic fertilizer rice is 2.65. BEP price of organic fertilizer rice Rp2.220 and non-organic fertilizer rice Rp2.157.
Keywords: farm analysis; production; income; return cost ratio; break even point